The University Students Experiences in Designing a Digital Multimodal Learning Media for Teaching - Nadilla Dwi Haerani; Afiyattena, Nurul; Sumedi, Siti Hanna (Indonesian Journal of Education and Learning, 2025)
Recently, designing a digital multimodal learning media is a must for interesting and effective teaching. Likewise, this study aimed to explore students' experience in designing digital multimodal learning media. A narrative study was conducted to dig into eight students' experiences in a private university in Banten Province. Data were collected through interviews, students' reflective journals, and documentations to gain deeper insights and were analyzed using Thematic analysis by Braun and Clarke (2006). The finding revealed three students’ experiences: 1) Most students have a variety of backgrounds related to the use of digital media, such as having taught using digital media in school and having knowledge of designing digital media projects from lecturers in class, but they rarely attend any digital learning seminars or workshops that can help them operate digital media. 2) The majority of students used and experienced the Canva application; 3) From the 12 multimedia design principles, only 7 were implemented by students, including multimedia, coherence, personalization, spatial contiguity, segmentation, pre-training, and modality. These findings suggest that educators and learners should consider digital media design principles when creating content, highlighting the importance of a multimodal approach.